Effects of vitamin E supplementation of a high-lipid diet on the growth and biochemical parameters of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus) - Huang, Weibin; Yan, Xiaobo; Liu, Hao; Tan, Beiping; Suo, Xiangxiang; Pan, Simiao; Li, Tao; Yang, Yuanzhi; Dong, Xiaohui (Frontiers in Marine Science, 2022)
There is a trend towards using high-lipid diets in aquaculture, which can be optimized by using certain additives. This study investigated the effect of vitamin E (VE) supplementation of a high-lipid diet on the growth, serum and liver biochemical indexes, hepatic histology, and lipid metabolism of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂Epinephelus lanceolatus). Six groups of iso-protein (50.23%) and iso-lipidic high-lipid (15.36%) experimental diets were prepared by adding VE at concentrations of 49.6 (basic diet, controls), 100, 110, 163, 206, and 245 mg/kg. Each treatment consisted of three replicates and 30 fish (10.20 ± 0.02 g) in an 8-week feeding experiment. The results show that 1) compared with controls, growth performance was not affected by VE addition. However, the weight gain rate (WGR) and specific growth rate (SGR) were significantly lower in the high-VE group (245 mg/kg) than in the 163 and 206 mg/kg groups. 2) Compared with controls, VE significantly increased the contents of alpha-tocopherol in the liver and muscle. 3) Adding VE can reduce the fatty livers caused by high-lipid diets and significantly reduce total serum cholesterol, reduce the activity of lipid synthesis enzymes, and significantly increase the activity of lipolytic enzymes in the liver. 4) Compared with controls, appropriate amounts of VE significantly increased the expressions of the liver lipid-metabolism-related genes PPAR-α, PPAR-β, PPAR-γ, H-FABP , A-FABP, and L-FABP. Based on observations of lipid metabolism enzyme activity, histological sections, and lipid-metabolism-related gene expression, we conclude that the addition of 163–206 mg/kg VE to a high-lipid diet can promote lipid metabolism in groupers.